2015
DOI: 10.4000/ejas.10761
|View full text |Cite
|
Sign up to set email alerts
|

The Nurse, the Veteran, and the Female Scientist: Dependency and Separation

Abstract: women into a position of power and authority that during the antebellum period they had only known, perhaps, in private. Between 1861 and 1865 more than twenty thousand women in the Union and Confederate states engaged in government and regimental Civil War hospitals, both as nurses and matrons. By fighting "disease, infection, and the medical infrastructure itself" they combined the nineteenth-century ideal of born nurturers with a new "soldierly aura" (Schultz, Women at the Front 3). By mid-war this somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As mentioned earlier, some roles within the military appear more acceptable for women and usually attract a higher proportion of female recruits. Women in medical, nursing, or caring roles are generally accepted as they conform to the stereotypical role of women and war (Brintlinger, 2017; Twelbeck, 2015). Burkhart and Hogan (2015) observed that women in roles such as these appeared to experience the same trauma and combat exposure as that of their male colleagues, but less abuse than those women serving in historically male roles.…”
Section: What the Literature Saysmentioning
confidence: 99%
“…As mentioned earlier, some roles within the military appear more acceptable for women and usually attract a higher proportion of female recruits. Women in medical, nursing, or caring roles are generally accepted as they conform to the stereotypical role of women and war (Brintlinger, 2017; Twelbeck, 2015). Burkhart and Hogan (2015) observed that women in roles such as these appeared to experience the same trauma and combat exposure as that of their male colleagues, but less abuse than those women serving in historically male roles.…”
Section: What the Literature Saysmentioning
confidence: 99%